Lactic acid production from potato waste using Response Surface Methodology (RSM) / Zafirah Zenol Abidin, Nurul Diyana Abdullah Sham and Siti Roshayu Hassan - Zenol Abidin, Zafirah; Abdullah Sham, Nurul Diyana; Hassan, Siti Roshayu (Faculty of Applied Sciences, 2023)
Lactic acid is an organic acid produced by microorganisms that ferment in glucose. Lactobacillus spp. is a type of lactic acid bacteria used to ferment lactic acid. Lactobacillus spp. are rod-shaped, gram-positive bacteria that do not produce spores. Because of the increased energy production, a carbohydrate or glucose source is essential for glycolysis and fermentation processes. Lactic acid is now widely used in pharmaceutical, food, and biodegradable polymer industries. Hence, this study aims to analyze the effect of two different parameters on the yield of lactic acid by using Response Surface Methodology (RSM). Secondly, this study also determined lactic acid concentration from potato waste using simultaneous saccharification and fermentation. It evaluated the effect of different concentrations of enzymes and the reaction time of fermentation on the yield of lactic acid. The SFF method was used in this study to produce lactic acid from potato waste. RSM was tasked with studying two different parameters using CCD. The concentration of enzyme at 1.5 g/L and the time for fermentation on day 1 produced the best result in this study, with the highest lactic acid production yield of 33.2%. These findings suggest that potato waste hydrolysate, like carbon sources, can replace synthetic glucose in producing lactic acid in the presence of enzymes. This process can be scaled up in a pilot plant.